KONTRIBUSI ANGKATAN MUDA PARTAI GOLKAR (AMPG) DALAM MEMBANGUN KESADARAN POLITIK GENERASI MUDA DI LAMPUNG - Femas Erlangga Dwi Saputra; Theresia Nicky Apika Dianggera; Anis Sri Wijayanti; Rima Yuni Saputri; Ana Mentari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
AMPG, as the youth wing of the Golkar Party, plays a vital role in youth development by providing political education, leadership training, and social programs that engage young people in local political dynamics. This study aims to analyze the contribution of the Young Generation of the Golkar Party (AMPG) in building political awareness among the youth in Lampung Province. The research uses a qualitative approach with a descriptive method, conducted through interviews with AMPG leaders to explore their role in fostering political awareness among young people. The findings indicate that AMPG has successfully addressed the challenge of low youth interest in political issues by utilizing social media, organizing leadership training, and introducing entrepreneurship programs. AMPG is also actively involved in youth character-building activities. Its contribution to developing political awareness among the younger generation is significant in shaping future leaders with integrity and active engagement in the political process..